Multi-decade catches of manta rays (Mobula alfredi, M. birostris) from South Africa reveal significant decline - Carpenter, Michelle; Parker, Denham; Dicken, Matthew L.; Griffiths, Charles L. (Frontiers in Marine Science, 2023)
Manta rays (Mobula alfredi and M. birostris) are poorly understood in South Africa, despite their ecological importance and charismatic appeal. This study analyzed a 41-year dataset from the KwaZulu-Natal bather protection program to investigate catch per unit effort between 1981-2021. We used Generalized Additive Models and the probability of encounter to assess annual and seasonal trends, as well as the effect of location and moon phases on catch rates. We also evaluated the size composition and demographics of caught manta rays using the same dataset. Our analysis revealed a significant decline in overall manta ray catches since the late 1990s (p<0.0001), with increased catch rates during summer, suggesting seasonal visitation to South African waters. We found that manta rays were caught at least once in all 46 netted beaches along the 350 km span of coastline, but with significantly more catches in the Central Area, between Anstey’s beach in the north and Mtwalume in the south. We also observed that moon phase had an effect on manta ray presence, with significantly more catches during spring tides at new and full moon phases. Over half of the caught individuals were juveniles, and a total of 841 individuals (52% of the total catch) belonged to the confirmed juvenile size class (1400-2500 mm disc width). We further found that a greater proportion (70%) of juveniles were caught in the southernmost sampled area, from Hibberdene in the north to Mzamba in the south. These findings highlight the importance of South African waters as a seasonal habitat for manta rays along the southern African coastline. The significant decline and spatial-temporal patterns we observed have critical implications for management and conservation efforts. Our study provides valuable baseline data for future research and underscores the need for continued monitoring and protection of these iconic marine species.